2021—How Do I Legally Sell Meat from My Own Livestock and Poultry in Florida? - Charles Carr; Jason Scheffler; Matthew Johansson (EDIS, 2021)
This publication provides information for Florida residents who want to sell meat and poultry from their own livestock and poultry. Written by Chad Carr, Jason Scheffler, and Matthew Johansson, and published by the UF/IFAS Department of Animal Sciences, revised August 2021.